2019
DOI: 10.1002/ccr3.2475
|View full text |Cite
|
Sign up to set email alerts
|

Primary signet ring cell carcinoma of the pancreatic head: A case report

Abstract: Pancreatic SRCC is a rare, aggressive tumor. Given limited evidence and the risk of side effects, physicians may elect to withhold chemotherapy in select patients, with the exception of neoadjuvant chemotherapy use to facilitate resectability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…PPSRCC of the pancreas is a rarely reported subtype of pancreatic adenocarcinoma with only 10 other case reports found in the literature (Table 1). [11][12][13][14][15][16][17][18][19][20] A recent study analyzing surveillance, epidemiology, and end results program (SEER) data found 497 cases of PPSRCC from 1973 to 2018. 5 Over 90% of signet ring cell carcinomas (SRCCs) are gastric cancers, and it is estimated that up to 28.2% of primary gastric cancers are in fact SRCCs.…”
Section: Discussionmentioning
confidence: 99%
“…PPSRCC of the pancreas is a rarely reported subtype of pancreatic adenocarcinoma with only 10 other case reports found in the literature (Table 1). [11][12][13][14][15][16][17][18][19][20] A recent study analyzing surveillance, epidemiology, and end results program (SEER) data found 497 cases of PPSRCC from 1973 to 2018. 5 Over 90% of signet ring cell carcinomas (SRCCs) are gastric cancers, and it is estimated that up to 28.2% of primary gastric cancers are in fact SRCCs.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study using the Surveillance, Epidemiology, and End Results database from 2000 to 2014, the incidence of pancreatic SRCC is 0.4-0.5% among all cases of pancreatic carcinoma [1]. Among the eight cases reported thus far (Table 1) [4][5][6][7][8][9][10][11], surgical treatment with radical resection, pancreatoduodenectomy, and/or total pancreatomy could be performed in four cases, and there was only one case of borderline-resectable tumor treated with neoadjuvant chemotherapy with gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…Signet ring cell carcinoma (SRCC) of the pancreas was an exceedingly rare histological subtype of pancreatic cancer, accounting for <1% of pancreatic cancers [14]. Because of the rarity of histological subtype, previous studies always reported the trends of incidence and predictors of pancreatic SRCC.…”
Section: Discussionmentioning
confidence: 99%
“…For pancreatic SRCC, Kaji et al [12] reported one case that three chemotherapy program was performed following by etoposide and cisplatin (EP therapy),S-1 monotherapy ,albumin-bound paclitaxel and gemcitabine. Dheeraj et al [14] reported that borderline resectable disease should still be considered for neoadjuvant chemotherapy to facilitate potential resectability. Based on these ndings, we thought that it seems chemotherapy based on gemcitabine could be used as a bene cial attempt for the treatment of patients if patients could tolerate the chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation